Prevalence and determinants of peripheral neuropathy among diabetics in a rural cum costal area of Villupuram district, Tamil Nadu - H, Sankari Mansa Devi; R, Vishnu Prasad; Bazroy, Joy; Singh, Zile (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes mellitus is characterised by persistent hyperglycaemia that may be due to absolute or relative insulin deficiency. It was estimated that there would be 285 million diabetics by 2010 in the world. This estimate is projected to increase by 65% to become 438 million in the year 2030. Similarly in India it is estimated to increase by 58% from 51 million people in the year 2010 to 87 million people by the year 2030. Methods: The study was carried out as cross sectional study among 235 diabetic OPD attendants of rural health centre aged 30 years and above. TCSS was used for diagnosis diabetic peripheral neuropathy. Data was entered in MS excel 2007 and analysis was done using SPSS version 17.0. Chi square test was applied to find statistical difference in proportions and a p value of <0.05 was considered statistically significant. Results: The overall prevalence of peripheral neuropathy among the study participants was observed to be 13.2%, while none of the study subjects presented with severe form of the disease. Nearly half of the patient who participated in the study also had co existing systemic hypertension. Also 12.3% of the study subjects had a positive history of foot ulcers. Conclusions: The prevalence of DPN increased with increasing age and it is observed to be associated with duration of diabetes, physical activity, smoking habit and systemic hypertension.